1999
DOI: 10.3168/jds.s0022-0302(99)75243-4
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Sources of Phenylalanine, Tyrosine, Lysine, and Methionine for Casein Synthesis in Lactating Goats

Abstract: The contribution to casein biosynthesis of peptides derived from blood was examined in late lactation goats (254 to 295 d in milk). Ratios of mammary uptake of free amino acids (AA) in blood to output of AA in milk protein and ratios of the enrichments of Phe, Tyr, Met, and Lys at isotopic plateau in secreted milk casein to the free AA in arterial and mammary vein blood were monitored during the last 5 h of a 30-h continuous i.v. infusion of [1-13C]Phe, [2H4]Tyr, [5-13CH3]Met, and [2-15N]Lys on two occasions: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 36 publications
5
41
0
Order By: Relevance
“…delivery from red blood cells [33,45] or from peptide breakdown. The putative contribution from peptides to milk phenylalanine and tyrosine has been shown to increase as the arterial supply of the free amino acids decreased in lactating goats [5]. In the current study, therefore, the peptide contribution to milk methionine and histidine may be a consequence of their low arterial concentrations as a free source.…”
Section: Mammary Metabolismmentioning
confidence: 70%
“…delivery from red blood cells [33,45] or from peptide breakdown. The putative contribution from peptides to milk phenylalanine and tyrosine has been shown to increase as the arterial supply of the free amino acids decreased in lactating goats [5]. In the current study, therefore, the peptide contribution to milk methionine and histidine may be a consequence of their low arterial concentrations as a free source.…”
Section: Mammary Metabolismmentioning
confidence: 70%
“…This suggests that in the high-CP diets, as a result of greater amounts of absorbed CP, larger plasma pools of AA occurred. Larger plasma fluxes of Phe, Met and Lys were observed when Phe or Lys plus Met were infused intravenously into dairy goats at different stages of lactation (Bequette et al, 1999;Mabjeesh et al, 2000). Despite the apparent evidence of more EAA absorbed in the high-CP diets and during LM infusion, milk production was similar among treatments, raising the question of the metabolic fate of these AA at the mammary gland and whole body levels.…”
Section: Discussionmentioning
confidence: 88%
“…Plasma flow measured in this study might be over estimated because certain amount of Phe and Tyr (up to 11% for Phe and 25% for Tyr; Bequette et al, 1999) might be taken up across the mammary gland as plasma-circulating peptides. In order to compare uptake of EAA across the mammary gland, however, it was assumed that the experimental accuracy was similar for all treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient uptake of isoleucine and leucine seen in this study suggests that the methionine based blood flow calculations may be underestimating the contribution of the plasma free AA to milk protein output, and that plasma flow was underestimated using this method. Some of this apparent deficit could be reduced by the use of alternative sources of AA, such as erythrocytes and peptides, and there is evidence of AA supply from these sources in studies by Bequette et al (1999) and Pacheco-Rios et al (1999). Pacheco-Rios et al (1999) demonstrated that AA uptake from plasma was insufficient for milk protein output of histidine, lysine, phenylalanine and tyrosine in pasture-fed cows in early lactation.…”
Section: Discussionmentioning
confidence: 99%
“…For histidine, there was a deficit in both plasma and blood, and it appears that for this AA, the blood supply may not be the only precursor pool (Pacheco-Rios et al, 1999). In lactating goats, Bequette et al (1999) showed that between 5% and 25% of the supply of lysine, methionine, phenylalanine and tyrosine for casein synthesis came from circulating peptides. These may be some of the mechanisms that support milk Regulation of mammary amino-acid metabolism by insulin protein output when precursor supply is insufficient, such as in early lactation or with restricted feed.…”
Section: Discussionmentioning
confidence: 99%